ANALYSIS OF FACTORS INFLUENCING CONSUMER DECISIONS WHEN CHOOSING LIEN SERVICES AT PEGADAIAN PUBLIC CORPORATION IN EAST LOMBOK - Handry Sudiarta Athar (Dinasti Publisher, 2020)
The aim of this study was to determine whether the interest rate variables, loan procedures, services, credit guarantees and facilities influence the customer's decision to pledge his goods at the Pegadaian Public Corporation in East Lombok. This research is a descriptive research with research location on the 23rd education road in Aikmel, East Lombok. The data collection method is a sample with a sample of 100 respondents, determined on the basis of unintended samples with the Slovenian formula. Techniques for data collection are observation and interview. Data collection tool is a questionnaire. The type of data used is quantitative data and qualitative data with data sources in the form of primary and secondary data. Based on the factor analysis, it has been found that out of the five factors investigated, four factors influence the customer's decision to pledge the goods, grouped into 3 core factors: the first factor has an own value of 1,703, a combination of variations in credit facilities and guarantees. The second factor has an eigenvalue of 1,022, in particular from the loan procedure variable. The third factor has an eigenvalue of 1.003, which is an interest rate variable. And the factor that has the greatest influence is the first factor because it has the highest self-esteem.